Analysis of Adolescent Self-Concept Development in Sidoarjo Regency Through Social Media Instagram - Vany Amelia Irwandi; Nur Maghfirah (Universitas Muhammadiyah Sidoarjo, 2022)
In this modern era, the role of social media is very influential, because social media is a medium that helps someone to interact with other people over long distances. And one of the most popular social media is Instagram. Instagram prioritizes the image feature as a display that is favored by many people, ranging from small children, teenagers and even parents. Based on these advantages, researchers want to investigate more about the role of Instagram to find out and describe the form of self-concept of adolescents in Sugihwaras Village, Candi Sidoarjo through Instagram social media. The method used in this study is a descriptive method with a qualitative approach. Data collection techniques carried out by researchers in the form of interview techniques (interviews) as the validity of the data. Sources of data used in this study are primary data and secondary data. Primary data obtained by researchers through interviews, observations, and documentation to informants, namely teenagers from Sugihwaras Village, Candi Sidoarjo. Secondary data obtained by researchers through evidence in the form of notes and reports. The subjects used in this study are profiles of teenagers listed on Instagram, images / photos that are often uploaded, search menu. While the object of this research is the self-concept that exists in adolescents who will be studied in Sugihwaras Village with certain criteria, namely adolescents aged 13-21 years.